Endoscopic treatment of Zenker’s diverticulum with Ligasure: simple, safe and effective - Diez Redondo, Pilar; Núñez Rodríguez, Henar; de Benito Sanz, Marina; Torres Yuste, Raúl; Pérez-Miranda, Manuel (Endoscopy International Open, 2019)
Background and study aims Zenker's diverticulum may cause disabling symptoms, especially in the elderly. Treatment has changed in recent decades from open surgery to management with flexible endoscopy, resulting in lower morbidity and mortality. The goal of this study was to present the largest series, with the longest follow-up, of patients with Zenker's diverticulum receiving outpatient treatment with flexible endoscopy using a diverticuloscope and Ligasure (Covidien, Minneapolis, Minnesota, United States), a device that allows tissue sealing and coagulation of vessels before cutting the septum between the diverticulum and esophagus.Patients and methods We performed 79 diverticulotomies in 69 patients (65.2 % male, mean age 73.4 years). The mean diverticulum size was 2.8 cm. In three cases with a diverticulum ≤ 1.5 cm, the diverticuloscope could not be placed. Results The technical success was 95.83 % and the clinical success 96.7 %: 84 % of the 56 patients followed for a mean of 34.6 months (24 – 64 months) had no dysphagia. The recurrence rate was 10.4 %, with a good response to a second diverticulotomy at 12 months (IQR: 11.5 – 17) in most cases. The most severe complications were two microperforations, resolved with conservative treatment, and one case of delayed bleeding endoscopically-controlled with a clip.Conclusions Diverticulotomy of the esophageal-diverticular septum with Ligasure is an outpatient endoscopic technique that is simple, effective in the long term and very safe for the treatment of patients with Zenker's diverticulum. In symptomatic recurrences, a second procedure was equally safe and effective in most patients.